2016
DOI: 10.1007/s00417-016-3526-4
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-accommodation in non-amblyopic children after bilateral cataract surgery and implantation with a monofocal intraocular lens: prevalence and possible mechanisms

Abstract: Pseudo-accommodation has a high prevalence among non-amblyopic pseudophakic children. Several possible mechanisms have been found to explain pseudo-accommodation in children: a high power of the IOL and a small axial length, maximizing the effect of the IOL shift, corneal multifocality and corneal higher-order aberrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…16 Using a ray-tracing equation, they suggested that when the IOL optic moves forward by 1 mm, the pseudoaccommodation is 0.8 D in long eyes and 2.3 D in short eyes. 16 They also found that the effect of IOL shift on the amplitude of accommodation depends 23 Atchison also proposed an equation for pseudoaccommodation which depended on 4 parameters: range of IOL movement, IOL position, keratometry, and AL. 24 However, other studies have found some correlation between preoperative AL and pseudoaccommodation through IOL movement with in-the-bag IOL fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Using a ray-tracing equation, they suggested that when the IOL optic moves forward by 1 mm, the pseudoaccommodation is 0.8 D in long eyes and 2.3 D in short eyes. 16 They also found that the effect of IOL shift on the amplitude of accommodation depends 23 Atchison also proposed an equation for pseudoaccommodation which depended on 4 parameters: range of IOL movement, IOL position, keratometry, and AL. 24 However, other studies have found some correlation between preoperative AL and pseudoaccommodation through IOL movement with in-the-bag IOL fixation.…”
Section: Discussionmentioning
confidence: 99%
“…In children, Denier et al found larger IOL power and smaller AL in the group with pseudoaccommodation. 23 Atchison also proposed an equation for pseudoaccommodation which depended on 4 parameters: range of IOL movement, IOL position, keratometry, and AL. 24 However, other studies have found some correlation between preoperative AL and pseudoaccommodation through IOL movement with in-the-bag IOL fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that pseudoaccomodation with a monofocal IOL is more prevalent in pseudophakic non-amblyopic children than adults (90% vs 7%). 35 This phenomenon is attributable to the smaller axial length, higher IOL power, corneal higher-order aberrations and maximized IOL shift in children as compared to adults. This at least partly explains the reluctance of most surgeons to shift from monofocal to multifocal IOLs in children.…”
Section: Multifocal Intraocular Lensesmentioning
confidence: 99%
“…Compliance issues with spectacles is another concern, more so in syndromic children. 4,5 In recent years, multifocal intraocular lenses (IOLs) have been attempted in the pediatric population in an attempt to restore the accommodation and achieve better stereopsis; however, the associated challenges like IOL power calculation, surgical complications and need for re-surgery have not been studied in detail. 6,7 The next major challenge of pediatric cataract surgery is confronting the accompanying astigmatism.…”
Section: Introductionmentioning
confidence: 99%